2010
DOI: 10.4037/15597768-2010-1005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography Versus Chest Radiography After Chest Tube Removal for the Detection of Pneumothorax

Abstract: Bedside ultrasound technology is as accurate as chest radiography in detecting pneumothorax following chest tube removal and can save institutions' time and money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A notable exception was reported from Henry Ford Hospital, noting complete agreement (kappa = 1.0) between ultrasound of the supine chest versus CXR (posture unstated) for detecting PTXs after TT removal, leading the authors to conclude that this would be costsaving. 14 It is notable that the examiners who attended the patient's bedside each had greater than 300 examinations prior to the study, whereas our bedside practitioners were novices. We hypothesized that if an ultrasound expert could mentor novice bedside personal that patient safety could be maintained and yet consume fewer resources.…”
Section: Introductionmentioning
confidence: 99%
“…A notable exception was reported from Henry Ford Hospital, noting complete agreement (kappa = 1.0) between ultrasound of the supine chest versus CXR (posture unstated) for detecting PTXs after TT removal, leading the authors to conclude that this would be costsaving. 14 It is notable that the examiners who attended the patient's bedside each had greater than 300 examinations prior to the study, whereas our bedside practitioners were novices. We hypothesized that if an ultrasound expert could mentor novice bedside personal that patient safety could be maintained and yet consume fewer resources.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong association between ultrasound and chest X‐ray with a therapeutic agreement of 97% 21 . There is perfect agreement between the two methods with a κ statistics value of 1.000 15 …”
Section: Resultsmentioning
confidence: 90%
“…After the full‐text screening, 18 studies were included in the systematic review. Eleven studies were conducted in the United States of America, 1–3,7,10–16 four studies in the United Kingdom, 17–20 one in the Netherlands, 5 one in Germany, 21 and one in Iran 6 (Table 1). No other studies were identified through manual screening of references of the included studies and relevant reviews.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations